2014
DOI: 10.1128/jvi.01906-14
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Herpes Simplex Virus 2 gD Bound to Nectin-1 Reveals a Conserved Mode of Receptor Recognition

Abstract: Herpes simplex virus 1 (HSV-1) and HSV-2 are among the most prevalent human pathogens. Both viruses can recognize, via the surface envelope glycoprotein D (gD), human nectin-1 as a functional receptor. Previous studies have successfully elucidated the molecular basis of the binding between HSV-1 gD and nectin-1 by cocrystallography. Despite a high sequence identity between HSV-1 and HSV-2 gDs, the atomic intermolecule details for the HSV-2-gD/nectin-1 interaction remain elusive. Here, we report the crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 64 publications
3
48
0
1
Order By: Relevance
“…Following the same strategy, we successfully expressed and purified a truncated PRV gD protein spanning residues 1-337 (hereafter referred to as gD337) using a baculovirus expression system (Fig 2A and 2B). Noted that the residue numberings for HSV gD in previous structural studies are based on the mature protein [21,22], the numberings for PRV gD amino CHO-K1 cells were transfected for transient expression of HU-, SW-nectin-1 and HU-HVEM, and subsequently infected with a PRV vaccine strain. Clear cytopathic changes were observed with HU-and SWnectin-1, which are marked with arrows.…”
Section: Prv Gd Engages Human and Swine Nectin-1 With A Similar Bindimentioning
confidence: 99%
See 2 more Smart Citations
“…Following the same strategy, we successfully expressed and purified a truncated PRV gD protein spanning residues 1-337 (hereafter referred to as gD337) using a baculovirus expression system (Fig 2A and 2B). Noted that the residue numberings for HSV gD in previous structural studies are based on the mature protein [21,22], the numberings for PRV gD amino CHO-K1 cells were transfected for transient expression of HU-, SW-nectin-1 and HU-HVEM, and subsequently infected with a PRV vaccine strain. Clear cytopathic changes were observed with HU-and SWnectin-1, which are marked with arrows.…”
Section: Prv Gd Engages Human and Swine Nectin-1 With A Similar Bindimentioning
confidence: 99%
“…It is demonstrated that the gD proteins of these alphaherpesviruses bind to nectin-1 with nanomolar affinities [13,19]. The detailed binding mode between HSV gD and human nectin-1 has been successfully illustrated in several previous studies [20][21][22]. The gD molecule is composed of a V-set Ig-like (or IgV-like) core and long N-and C-terminal extensions, It utilizes both terminal-extension elements to interact with nectin-1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To this regard, it is important to point out that the side guanidine groups of AGMA1 might reinforce membrane interactions, thanks to their well-known chaotropic properties [28,36,64]. Interestingly are also the observation that the binding of HSV-1 and 2 glycoproteins gD to nectin-1 depends on several basic amino acids, including L25, R36, R134 and R222 [65] and that HSV-2 infection can be mediated by a v b 3 integrin [66] that is well known to bind its physiological or pathological ligand via basic domains [67e69]. Taken together, these data suggest that the high positive charge of AGMA1 may mediate its binding to receptors different from HSPGs, conferring to the polymer a "multitarget" mechanism of action, as already demonstrated for cationic dendrimer-like compounds [70].…”
Section: Tablementioning
confidence: 99%
“…HSV gD binds to both HVEM and nectin-1, and this step is essential for HSV infection of cells. The HVEM and nectin-1 binding domains of HSV gD are located in different regions of the glycoprotein: the HVEM binding domain is at the N terminus (26)(27)(28), and the nectin-1 domain is in the middle of HSV gD (28)(29)(30). Mutations in one domain can impair the ability of HSV gD to use one receptor but not the other receptor (28,31,32).…”
mentioning
confidence: 99%